An Analysis of Abstract Translation by Pohuwato University Students: Translation Techniques, Quality, and Local Academic Register - Hisasmaria Hisasmaria; Idrus Dama (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
This study investigates how undergraduate students at Pohuwato University translate their thesis abstracts from Indonesian into English, focusing on the translation techniques employed, the quality of the translated texts, and the academic register reflected in the target texts. Abstracts are a crucial component of academic writing because they provide a condensed representation of the aims, methods, findings, and implications of a study, and their quality often determines whether a paper will be read, cited, or accepted for wider publication. Previous studies on student and journal abstracts in Indonesia indicate that translation is typically dominated by literal translation, borrowing, calque, and transposition, yet recurrent problems remain in accuracy, acceptability, and readability of the English versions. Addressing this gap, the present study offers novelty by integrating analysis of translation techniques and translation quality with an explicit examination of local academic register as manifested in Pohuwato University students' abstracts — a context largely neglected in prior Indonesian academic translation research. This descriptive qualitative study uses 10 pairs of Indonesian–English thesis abstracts (120 translation units) as data. The analysis identifies translation techniques based on Molina and Albir's taxonomy, assesses accuracy, acceptability, and readability using a three-point scale, and interprets academic register patterns in the translated texts. Findings show that literal translation dominates at 43.3%, followed by borrowing (17.5%), transposition (11.7%), and other techniques. Overall translation quality falls within the "fair to good" range, but approximately 10–14% of units are inaccurate, unacceptable, or difficult to read. Academic register analysis reveals persistent Indonesian rhetorical influence in verb choices, sentence length, and tense inconsistency. The study recommends data-driven, institution-specific pedagogical intervention to strengthen academic English writing and translation at Pohuwato University.